Comparison of Dentoskeletal and Periodontal Changes in Patients with Maxillary Arch Constriction Using Acrylic versus Clear Polycarbonate Removable Plate Appliances (Essix) with Midline Screw - Majid Azizi; Atefe Ataie; Mohammad Mostafay; Narges Deimeh (Mashhad University of Medical Sciences, 2024)
Background: Many types of maxillary expansion devices with different expansion rates are used in the treatment of maxillary arch constriction. This study aimed to assess the effectivenessof a new removable plate appliance to improve maxillary arch constriction in comparison to similar common devices.Methods and Materials: The present quasiexperimental study was conducted on 15 patients who had referred to the dental clinic of Birjand University of Medical Sciences between July 2020 and December 2021. In the case group, the maxilla was widened with a transparent removable plate made of thermoplastic plates without wire components. The information of patients in the control group (treated with the removable acrylic plate with a midline screw and wire components) was extracted from a similar study. Data were subjected to statistical analysis using SPPS version 25. T-test, Mann-Whitney and one-sample T-test were used to compare groups. P-value less than 0.05 was considered statistically significant.Results: The average amount of monthly intermolar expansion was 0.871±0.552 and 1.156±1.09 mm in the case and control groups, respectively. The mean amount of monthly inter-canine expansion was 0.994±0.498 mm and 0.931±0.869 mm in the case and control group, respectively. The results indicated no significant difference between the two study groups in terms of intermolar expansion (P=0.07) and intercanine expansion (P=0.68). The degree of satisfaction with the treatment was significantly higher in the case group, compared to the control group (P=0.01).Conclusion: It seems that the transparent thermoplastic removable plate without wire components is not more effective in the treatment of patients with maxillary arch stenosis compared to the common model with wire components. However, the use of this new device can be effective in increasing patients' satisfaction by maintaining the efficiency of treatment.